Lymphangioleiomyomatosis (LAM) Cell Atlas. Issue 1 (7th September 2022) - Du, Yina; Guo, Minzhe; Wu, Yixin; Wagner, Andrew; Perl, Anne Karina; Wikenheiser-Brokamp, Kathryn; Yu, Jane; Gupta, Nishant; Kopras, Elizabeth; Krymskaya, Vera; Obraztsova, Kseniya; Tang, Yan; et al.
Abstract : Lymphangioleiomyomatosis (LAM) is a rare lung disease of women, causing cystic remodelling of the lung and progressive respiratory failure. The cellular composition, microenvironment and cellular interactions within the LAM lesion remain unclear. To facilitate data sharing and collaborative LAM research, we performed an integrative analysis of single-cell data compiled from lung, uterus and kidney of patients with LAM from three research centres and developed an LAM Cell Atlas (LCA) Web-Portal. The LCA offers a variety of interactive options for investigators to search, visualise and reanalyse comprehensive single-cell multiomics data sets to reveal dysregulated genetic programmes at transcriptomic, epigenomic and cell–cell connectome levels.